Artificial Intelligence as a competitive advantage factor in the hospitality industry - Correia, Rita Maria de Almeida Leal da Rocha (2021)
This dissertation aims to understand the role of Artificial Intelligence in the costumer decision-making process to determine if AI is considered a competitive advantage factor in the hospitality industry. To this end, it is essential to study the potential customer profile to understand which characteristics and factors contribute to influence the choice of a hotel customer. The topic has been gaining space in different discussion environment and several questions have been raised and debated for a better understanding of this technology and its present and future implications. In order to achieve the main objective of this investigation, an exploratory study was carried out using a survey as a data collection method that was answered by 268 individuals. Also, an interview to the Evolution Lisboa Hotel Manager was conducted to study the hotel’s perception on the adoption of AI and its advantages and disadvantages. The data collected from the surveys was later analyzed using statistical methods. Through the analysis of these results, it is possible to deduce that AI is the least important feature in a hotel when it comes to the customer’s purchase decision making in the hospitality industry. However, nowadays individuals are willing to experience some AI tools if it does not interfere with the customer’s interaction with humans and when it is possible to exist a symbiosis between humans and machines.